Infraestructura vial y su incidencia en el desarrollo socioeconómico y territorial del cantón quinsaloma, año 2024 - Yunda Alvarez, Franklin Ernesto (2024)
The research project focuses on determining the impact of road infrastructure on the socioeconomic and territorial development of the canton of Quinsaloma, in the province of Los Ríos. Given that it is an agricultural and commercial canton, roads are key to generating growth and better living conditions for the population. The study makes a diagnosis of road infrastructure and socioeconomic conditions, identifying mobility limitations in order to propose strategies to optimize transportation and facilitate access to basic services. The research has a mixed quantitative and qualitative approach, is carried out in the territory and is descriptive and analytical in nature. The techniques employed for the collection of information include observation and the use of instruments such as interviews and surveys. The surveys and on-site visits allowed identifying the current state of the canton's road infrastructure, finding that more than a third of those surveyed stated that the roads are not in adequate conditions for mobilization. Seventy percent consider that external investment has been affected by the difficulty of accessing certain sectors of the rural area where there is a lack of drainage ditches, culverts, ballasted roads and roads in poor condition that make it difficult to move production in these sectors. It is proposed as a strategy to increase the frequency of monitoring and follow-up on the condition of roads that present special conditions in order to improve them.